Fiscal Performance and Financial Independence of Malang City Government (2020–2024): A Qualitative Assessment - Wahyudi, Untung; Zahroh, Viony Alfiyatu; Novitasari, Dewi (Badan Perencanaan Pembangunan Kota Malang, 2025)
This research examines the fiscal performance and financial independence of the Malang City Government from 2020 to 2024 through a qualitative descriptive analysis designed to reveal fiscal management dynamics under decentralization policy. The study uses official financial documents, statistical data, and policy analyses to evaluate fiscal effectiveness, efficiency, and flexibility within local governance. Findings reveal a positive trajectory of fiscal performance, with Regional Original Income (PAD) growing by 8.1% annually, although dependence on central transfers remains high at 62% of total revenue in 2024. The fiscal independence ratio rose from 29.3% in 2021 to 33.8% in 2024, supported by tax digitalization and service-based levy reforms. Malang City maintained an unqualified audit opinion (WTP) for fourteen consecutive years, reflecting transparent governance. The study concludes that sustainable fiscal capacity can be enhanced through diversified revenue generation rooted in digital and creative economies, improved fiscal oversight, and inter-regional collaboration. These insights contribute to understanding fiscal decentralization at the urban level.